2011
DOI: 10.1016/j.ejcts.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hemoglobin A1c predicts atrial fibrillation after off-pump coronary bypass surgery

Abstract: Preoperative hemoglobin A1c independently predicts the occurrence of AF after isolated off-pump coronary bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
4
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 18 publications
4
40
4
9
Order By: Relevance
“…Although it has been shown that higher HbA 1c values may decrease the risk of atrial fibrillation (30) and mortality in patients with acute hyperglycemia (31), we found only a nonsignificant trend for decreasing the risk of complications. The protective effect mentioned above and a decreased risk of hypoglycemic events could be an explanation for this phenomenon.…”
Section: Discussioncontrasting
confidence: 95%
“…Although it has been shown that higher HbA 1c values may decrease the risk of atrial fibrillation (30) and mortality in patients with acute hyperglycemia (31), we found only a nonsignificant trend for decreasing the risk of complications. The protective effect mentioned above and a decreased risk of hypoglycemic events could be an explanation for this phenomenon.…”
Section: Discussioncontrasting
confidence: 95%
“…[1][2][3] On the other hand, several studies in past years have found that higher HbA1c levels lead to adverse outcomes in patients. [8][9][10][11][12] The present study found that preoperative FBS levels have higher association with arrhythmia, atelectasis and prolonged mechanical ventilation while preoperative HbA1C levels are of higher association with IABP, massive bleeding (>1000 mL/24h) and multi-organ failure. Former studies suggest that preoperative higher blood glucose levels raise the risk of infection and tighten inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies identified the influence of diabetes in AF incidence, but results still controversial. (15,16) …”
Section: Discussionmentioning
confidence: 99%